Digital Comic Learning Media Based on Problem Based Learning on Respiratory System Science Material to Improve Students' Critical Thinking Skills: Indonesia - Ni Komang Ayu Isa Maharani; I Gede Astawan; Ni Ketut Desia Tristiantari (Thinking Skills and Creativity Journal, 2025)
This research was motivated by the low use of innovative learning media to enhance students' critical thinking skills in the respiratory system material. The aim of this study was to develop and test the effectiveness of a Digital Comic Media based on Problem-Based Learning (PBL). The development model used was ADDIE. The research subjects were fifth-grade elementary school students. Data were collected through questionnaires distributed to experts, teachers, and students, as well as through critical thinking skills tests. Data analysis was conducted using descriptive quantitative methods and t-tests to assess the media's effectiveness. The results showed that the Digital Comic Media was deemed appropriate based on expert evaluations of subject matter (average score of 3.67; classified as good), media experts (3.33; classified as good), student trials (3.78; classified as very practical), and teacher assessments (3.25; classified as very practical). The effectiveness test using a t-test showed a significance value of 0.941, leading to the rejection of H0 and acceptance of H1. Thus, the PBL-based Digital Comic Media was proven effective in improving students' critical thinking skills. The implication of this research is that digital comic media can be used as an innovative alternative in science learning to enhance student engagement and critical thinking skills, and it can serve as a reference for developing other learning media.